The Sequence of Loyalty and Filial Piety and Its Ideological Origins in the Traditional Ethical Culture of China and Japan - Yang, Weiyu (ETHICS IN PROGRESS, 2019)
The traditional ethical culture of Japan is under the influence of Chinese Confucian culture. However, due to differences in historical tradition and social structure, in traditional Japanese culture, “loyalty”, as the highest value, is in preference to “filial piety” and it lays a foundation for universal moral principles of the society; while in the Chinese Confucian culture, “filial piety” is regarded as the first and “loyalty” is the natural expansion of “filial piety”. The main reason is the influence of the indigenous Shinto in traditional Japanese culture. After the internalization of the indigenous Shinto and the Tennoism as well as the indoctrination of over 600-year ruling of the samurai regime, “loyalty”, as the national cultural and psychological heritage, has the religious and irrational mysterious color, which is different from the secularization and the practical rationality of the pre-Qin Confucian ethics of China. Loyalty to the emperor and devotion to public interests advocated by Bushido is an important characteristic of traditional Japanese ethical culture, and the religious and absolute understanding of “loyalty” is hidden with the risk of nationalism and irrationality.